Análise prognóstica da imunoexpressão de osteopontina no microambiente dos carcinomas mamários esporádicos de cadelas - Monteiro, Lidianne Narducci [UNESP] (2013)
Osteopontin (OPN) is a secreted glycophosphoprotein that has been implicated in a number of different normal physiologic and pathologic processes in humans. OPN is known to be involved in the progression and metastasis of various humans cancers, but this relation is still little explored in the veterinary literature. The aim of this study was to evaluate the expression of osteopontin in canine mammary carcinomas and its relation with well established canine mammary tumor biomarkers. For that, the expression of OPN, EGFR, HER2, and c-Kit were evaluated along with Ki67 rate in 43 mammary carcinomas from different female dogs. OPN was demonstrated to be expressed by neoplastic epithelial cells in all carcinomas as well as in stromal cells from the tumor microenvironment. Relation between OPN high expression and EGFR positivity (P < 0.001) and high HER2 expression (P = 0.012) was demonstrated. In conclusion, osteopontin seems to be related to poor prognosis and MAPK pathway activation, the latter a feature that could imply in the future use of treatments with drugs directed against this particular signaling pathway in highly OPN expressing canine mammary tumors